Expanding the inhibitor space of the WWP1 and WWP2 HECT E3 ligases - Ashley P. Dudey; Jake M. Rigby; Gregory R. Hughes; G. Richard Stephenson; Thomas E. Storr; Andrew Chantry; Andrew M. Hemmings (Taylor & Francis Group, 2024)
The HECT E3 ubiquitin ligases 1 (WWP1) and 2 (WWP2) are responsible for the ubiquitin-mediated degradation of key tumour suppressor proteins and are dysregulated in various cancers and diseases. Here we expand their limited inhibitor space by identification of NSC-217913 displaying a WWP1 IC50 of 158.3 µM (95% CI = 128.7, 195.1 µM). A structure-activity relationship by synthesis approach aided by molecular docking led to compound 11 which displayed increased potency with an IC50 of 32.7 µM (95% CI = 24.6, 44.3 µM) for WWP1 and 269.2 µM (95% CI = 209.4, 347.9 µM) for WWP2. Molecular docking yielded active site-bound poses suggesting that the heterocyclic imidazo[4,5-b]pyrazine scaffold undertakes a π-stacking interaction with the phenolic group of tyrosine, and the ethyl ester enables strong ion-dipole interactions. Given the therapeutic potential of WWP1 and WWP2, we propose that compound 11 may provide a basis for future lead compound development.